Test of the Effectiveness of Giving Salmon DNA Serum with Virgin Coconut Oil Extract on the Growth of Skin Tissue from Cut Scars on the Skin of Female Wistar Rats (Rattus Norvegicus) - Apriani, Silvi; Angie, Evelyn; Nasution, Syamsul Arifin (Journal La Medihealtico, 2024)
Various treatments can cure pockmarks. First, you have to know the cause of the pockmarks and the strength of the pockmarked skin, making it easier to choose the treatment, one of which is dermapen, which uses plasma from platelets. Test and compare the effectiveness of the derma pen action using platelet plasma with the derma pen action on the pockmarked skin surface of female Wistar rats (Rattus novergicus). This research is a laboratory experiment to compare the effectiveness of the dermapen action using plasma from platelets with the dermapen action on the pockmarked skin surface of female Wistar rats (Rattus novergicus) using a post-test with control group design or control samples based on treatment groups to analyze the dermapen action using plasma from platelets with dermapenic action on the surface of rat skin pockmarks. The results showed that the dermapen treatment group with plasma from platelets at a dose of 10% was more effective in healing cut wounds in white mice than the dermapen treatment group using plasma from platelets at doses of 2.5% and 5%. This is because, at a concentration of 10%, blood plasma metabolite compounds from platelets that are applied to wounds already affect the wound. The effect only inhibits microorganisms at small doses, making it less effective in healing wounds. It is recommended that the minimum dose be 10% so that the metabolite compounds in the plasma from platelets have a healing effect on wounds.